PATRIOTIC DEVELOPMENT AND NATIONAL SPIRITUALITY OF PERSONALITY IN THE CREATIVITY OF UKRAINIAN EDUCATION IN WESTERN UKRAINE - Bagriy, Mariya; Rozlutska, Galyna (Mountain School of Ukrainian Carpaty, 2020)
Тhe genesis of enlightenment in Western Ukraine suggests that this system is a peculiar model of socio-cultural conditions that arose in a society at a certain historical stage. Achievements of the Western Ukrainian intellectuals in the education of the studied period allow us to assert that the educational national system has deep historical roots, a solid scientific basis, and an extraordinary national tradition. The basis of the theoretical substantiation of the periodization of the genesis and evolution of the ideas of national identity, the awakening of the consciousness of the people, the education of a national conscious personality as the transitory motifs of Western literature of that period was marked by periodization, in which the main historical events and facts of the educational movement of the Western Ukrainian intellectuals are reflected. In the context of this, it should be noted that in the history of Ukraine of the previous period (XVI-XVII centuries), complex economic transformations and political events took place when another state strengthened and developed, and in Ukraine there was an active opposition of national minorities (including Ukrainians) against feudal, Polish-gentry enslavement and Catholicism. In this case, the emergence of classical education in Western Ukraine was preceded by a number of reasons of a religious nature (the imposition of Catholicism on the territory of the Ukrainian Orthodox Church), the activity of fraternities (as organizations contributing to the cultural, religious, and national liberation movement against opolaciation, Catholicism, cultural polonization, etc.) as well as cultural, historical, economic and social conditions of that period.